Increasing Community Awareness of the Calculation of Cost of Goods Sold for Banjarsari Tape Production Through the Development of a Dynamic Guidebook - Ningrum, Linda Agustin; Roziqin, Mohamad Firzon Ainur; Surya, Eka Putri; Prasetyo, Abdul Rahman; Aruna, Alby; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (Abdimas Indonesian Journal, 2024)
Increasing community awareness of the calculation of the Cost of Goods Sold (COGS) for tape production in Banjarsari through the development of a dynamic guidebook aims to enhance local producers' understanding and skills in accurately calculating COGS. This program involves creating an interactive and easy-to-understand guidebook, which includes steps for calculating COGS and the influencing factors. Methods include the preparation of guidebook materials, technical training for producers, and evaluation of the guidebook's effectiveness through user feedback. Results show a significant improvement in producers' ability to calculate COGS and manage production costs. The implementation of this program is expected to support the development of a more efficient and competitive tape industry in Banjarsari Village.